Implementasi Green Production dan Kapasitas Inovasi dalam Meningkatkan Daya Saing Industri Berkelanjutan - Nurhabibah Nurhabibah; Dita Rosyalita (Jujurnal Publisher, 2026)
This study addresses the issue that the implementation of Green Production is often assumed to yield sustainable competitive advantage, yet evidence shows that benefits are inconsistent and may not translate into long-term competitiveness without internal mechanisms. The purpose of this research is to explain the relationship between Green Production implementation, innovation capacity, and sustainable competitive advantage in the context of sustainable industrial competitiveness. The study employs a library research design using qualitative content analysis of relevant written literature, drawing on both primary and secondary sources related to the three keywords. The data consist of conceptual descriptions and explanations extracted from scholarly books, journal articles, and prior research that discuss Green Production practices, Innovation Capacity capabilities, and the multidimensional meaning of sustainable competitive advantage. The study concludes that sustainable competitive advantage is more likely to be achieved when Green Production is accompanied by strengthened Innovation Capacity, which enables organizations to convert operational green changes into valuable and enduring innovation outcomes.